UTILIZATION OF SALAK FRUIT PEEL AS ANTIBACTERIAL AGENTS FOR PSEUDOMONAS AERUGINOSA - Sutriana, Amalia; Perdana, Ananda Putra; Panjaitan, Budianto; Melia, Juli; Adam, Mulyadi (Buletin Veteriner Udayana, 2022)
Pseudomonas aeruginosa is an opportunistic pathogenic bacteria that can infect both human and animal. This bacteria has undergone Multi Drug Resistance caused by irrational use of antibiotics. Therefore, it is necessary to conduct research to obtain antibacterial compounds from natural ingredients, one of them is from salak fruit peel ( Salacca zalacca ). This study aims to investigate the antibacterial activity of salak fruit peel extract  in inhibiting the growth of P. aeruginosa in vitro . Salak fruit peel was extracted by maceration method using ethanol 96%. Concentrations of salak fruit peel extract used in this study were 5%, 10%, 20% and 30%. Disk containing chloramphenicol was used as positive control and aquadest was used as negative control. Antibacterial activity of salak fruit peel extract was conducted using Kirby-Bauer method. The data was analyzed descriptively. The results showed that there were no inhibition zone was formed surrounding the disc containing salak fruit peel extract at concentrations of 5%, 10%, and 20%. At concentration of 30%, the inhibition zone was formed with diameter 6.2 mm. It could be concluded that salak fruit extract at concentration less than 30% did not have antibacterial activity againts P. aeruginosa in vitro .